Technological Transposition of the Subject and the Work - Nowicki, Tomasz (INSTED: Interdisciplinary Studies in Education & Society, 2016)
The aim of the article is to show the trajectory of the development of relations between objects and the human in the context of posthumanism. I would like to show what challenges brought us new technologies and the change in the contemporary functioning of the subject, both in the material and discursive dimension.